Deconstructing Orientalism: Islamic Lessons in European Arts at the Turn of the Twentieth Century - Labrusse, Rémi (Manazir Journal, 2022)
This article has no intention to deconstruct the now classical Saidian idea that Western Orientalism was a global system of misrepresentation and control of non-Western cultures, particularly in the nineteenth century, when the colonial expansion spread over most of the regions marked by the cultures of Islam. Instead, It intends to reflect upon the fact that during this period, the Orientalist system established itself in the broader context of a modern condition which was (and still is) felt and conceived as a general “state of crisis.” This critical dimension of modern Western culture explains both the extreme degree of violence of the Orientalist enterprise of capture and its internal criticism by its own perpetrators. The same duality characterizes the modern production of visual images: the crisis of the Western mode of mimetic representation is responsible for both the paroxysmal multiplication of images, in the nascent “society of the spectacle,” and their implosion, in the experiments of the so-called artistic avant-gardes at the beginning of the twentieth century. Some decades earlier, such a radical critique of representation had been developed at the crossroads of applied arts and architecture, in debates on the nature and function of ornaments. We know how central the reference to the arts of Islam and their aesthetics, which were conceived in opposition to the contemporary Orientalist fancies, was for these debates. How did these two positions—the critique of Orientalism and of visual representation—interact? To what extent did they reinforce each other? In order to illustrate this question, This article will conjure up a most revealing episode: Henri Matisse’s trip to Algeria in 1906 and the works that immediately followed this early “Oriental” encounter for the artist.